Girl with xanthogranulomatous pyelonephritis and bronchiectasis: Case report. Issue 2 (16th April 2013) - Nadeem, Montasser; Oni, Oluwole A; Ryan, Martin; Puri, Prem; Coghlan, David; Greally, Peter
Abstract Xanthogranulomatous pyelonephritis (XGP) is a rare chronic inflammatory disorder of the kidney. Infiltration to lung and liver can occur. We present a rare complication of locally invasive XGP extending beyond the diaphragm to the lung to cause bronchiectasis in an adolescent girl with chronic productive cough, weight loss and no urinary symptoms. The patient underwent open left radical nephrectomy, where it was noted that the left kidney lay very high with significant perinephric inflammation and was densely adherent to the diaphragm and partially adherent to the spleen. XGP was confirmed on histology.